Don’t lose your progress!

We cover every section of the GMAT with in-depth lessons, 5000+ practice questions and realistic practice tests.

Up to 90+ points GMAT score improvement guarantee

The best guarantee you’ll find

Our Premium and Ultimate plans guarantee up to 90+ points score increase or your money back.

Master each section of the test

Comprehensive GMAT prep

We cover every section of the GMAT with in-depth lessons, 5000+ practice questions and realistic practice tests.

Schedule-free studying

Learn on the go

Study whenever and wherever you want with our iOS and Android mobile apps.

The most effective way to study

Personalized GMAT prep, just for you!

Adaptive learning technology focuses on your academic weaknesses.

Data Sufficiency: Plugging into Yes/No Data Sufficiency

Is $$y^{-x}$$ negative? >(1) $$y$$ is positive. >(2) $$x$$ is negative.
Correct. [[snippet]] Stat. (1): Since $$y$$ is positive, the fraction $$y^{-x}$$ is positive, so the answer is a definite "No." That is a definite answer, so **Stat.(1) → No → S → AD**. Stat. (2): You know that $$x$$ is negative, but that tells you nothing about $$y$$. * If you __Plug In__ $$y=3$$ and $$x=-3$$, then you get a positive number: >>$$y^{-x} = 3^{-(-3)} = 3^3 = 27$$. * If you __Plug In__ $$y=-3$$ and $$x=-3$$, then you get a negative number: >>$$y^{-x} = (-3)^3 = -27$$. There is no definite answer, so **Stat.(2) → Maybe → IS → A**.
Incorrect. [[snippet]] The base determines the sign when using exponents.
Incorrect. [[snippet]] Stat. (1): Since $$y$$ is positive, the fraction $$y^{-x}$$ is positive, so the answer is a definite "No." That is a definite answer, so **Stat.(1) → No → S → AD**.
Incorrect. [[snippet]] Stat. (2): You know that $$x$$ is negative, but that tells you nothing about $$y$$. * If you __Plug In__ $$y=3$$ and $$x=-3$$, then you get a positive number: >>$$y^{-x} = 3^{-(-3)} = 3^3 = 27$$. * If you __Plug In__ $$y=-3$$ and $$x=-3$$, then you get a negative number: >>$$y^{-x} = (-3)^3 = -27$$. There is no definite answer, so **Stat.(2) → Maybe → IS → ACE**.
Statement (1) ALONE is sufficient, but Statement (2) alone is not sufficient to answer the question asked.
Statement (2) ALONE is sufficient, but Statement (1) alone is not sufficient to answer the question asked.
BOTH Statements (1) and (2) TOGETHER are sufficient to answer the question asked, but NEITHER statement ALONE is sufficient to answer the question asked.
EACH statement ALONE is sufficient to answer the question asked.
Statements (1) and (2) TOGETHER are NOT sufficient to answer the question asked, and additional data specific to the problem are needed.